Raw material selection and furnace operation for optimal energy efficiency and silicon recovery in Ferro Silicon production - Hrefna Hallgrímsdóttir 1986- (2013)
At Elkem Iceland there are three submerged electrical arc furnaces. The last quarter of 2012 was the best performance on of the furnaces, Furnace 1. At the same time the electrodes moved excessively and the hypothesis was that the operations could be improved even more by reducing electrode movement. In the beginning of 2013 the operations started to worsen, the Specific energy consumption (SEC) increased and silicon recovery decreased. Electrode movements on the other hand decreased a lot. This thesis is a case study of why the electrode movements decreased and why operations went off track. Electrode movements were statistically compared to SEC, fixed carbon (FixC), furnace rotation and electrode slipping. The key parameters; SEC and silicon recovery were also statistically evaluated and compared to theoretical values. The conclusion was that the fixed carbon on the furnace was at some point increased above the optimum level causing the SEC to increase, the silicon recovery to decrease and to some extent reducing the movement of the electrodes. The SEC and silicon recovery got worse since too high carbon changes the balance in the chain of reactions in the furnace resulting in a buildup of silicon carbide (SiC) in the furnace. The high carbon content also reduces the resistance in the charge and thereby reducing the movement of electrodes. Another factor in the reduction of electrode movements is the elimination of over-control in the electrode slipping routines. The analysis was a learning curve for the process engineers at Elkem Iceland. It underlines the necessity of long term analysis of the furnaces and the introduction of the appropriate tools to do so. Elkem Ísland